2015
DOI: 10.1016/j.stem.2015.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of Phosphodiesterases 2A and 3A Underlies Compromised β-Adrenergic Signaling in an iPSC Model of Dilated Cardiomyopathy

Abstract: Summary β-adrenergic signaling pathways mediate key aspects of cardiac function. Its dysregulation is associated with a range of cardiac diseases, including dilated cardiomyopathy (DCM). Previously, we established an iPSC model of familial DCM from patients with a mutation in TNNT2, a sarcomeric protein. Here, we found that the β-adrenergic agonist isoproterenol induced mature β-adrenergic signaling in iPSC-derived cardiomyocytes (iPSC-CMs), but that this pathway was blunted in DCM iPSC-CMs. Although expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
136
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 161 publications
(162 citation statements)
references
References 43 publications
25
136
1
Order By: Relevance
“…iPSC can be propagated indefinitely, differentiated into EC and smooth muscle cells (11), and used for vascular disease modeling (12) and drug screening (13), as shown with iPSCderived cardiomyocytes (14,15).…”
mentioning
confidence: 99%
“…iPSC can be propagated indefinitely, differentiated into EC and smooth muscle cells (11), and used for vascular disease modeling (12) and drug screening (13), as shown with iPSCderived cardiomyocytes (14,15).…”
mentioning
confidence: 99%
“…Despite the immaturity of the derived hiPSC-CMs, this study paved the way for a subsequent study by Wu et al, which showed more mechanistically that the mutated TNNT2 caused the cardiomyopathic phenotypes by nuclear translocation, followed by epigenetic activation of the phosphodiesterase 2A/3A (PDE2A/PDE3A) genes leading to contractile dysfunction. 79 These studies demonstrated the ability of hiPSC technology to enable mechanistic studies on patient-specific cardiomyocytes.…”
Section: Disease Modeling Using Patient-specific Hipsc Derivativesmentioning
confidence: 96%
“…Using this approach, disease-contributing factors at the epigenetic level have been identified. For example, in an iPSC model of dilated cardiomyopathy with a mutation in the TNNT2 protein, it was found that phosphodiesterases (PDE) contribute to the disease and that the upregulation of PDE occurs as a result of decreases in a repressive histone modification (H3K27me3) at enhancers of PDE genes [10]. Studies such as this have contributed to the recent advances in our elucidation of aberrant signalling pathways in patients with specific cardiomyopathies.…”
Section: Targeting Patient-specific Cardiomyopathiesmentioning
confidence: 99%